THE INFLUENCE OF JOB CHARACTERISTICS ON EMPLOYEE PERFORMANCE WITH WORK MOTIVATION AS AN INTERVENING VARIABLE AT PT. PERKEBUNAN NUSANTARA VI - Putri Mariska, Ana Tasya; Sumarni, Sumarni; Rohman Willian (Yayasan Nuraini Ibrahim Mandiri, 2024)
This research aims to determine the influence of job characteristics on employee performance with work motivation as an intervening variable at PT. Perkebunan Nusantara VI. This type of research is quantitative research. The population in this study were all employees of PT. Perkebunan Nusantara VI, totaling 197 people with a sample of 67 people. Data was collected using a questionnaire. The data analysis method for this research is descriptive statistical analysis using the Structural Equation Model (SEM) technique, with Partial Least Square (PLS) as a tool for processing it using the SmartPLS program. The results of this study indicate that job characteristics have a positive and significant influence on employee performance, job characteristics have a positive and significant influence on work motivation, work motivation has a positive and significant influence on employee performance, job characteristics have a positive and significant influence on employee performance through work motivation. Keywords : Employee Performance, Job Characteristics, Work Motivation